TO THE ISSUE OF REDUCING ENVIRONMENTAL RISKS OF A TRANSPORT ENTERPRISE BASED ON RATIONAL NATURE MANAGEMENT - L. Makolova (Вестник университета)
The problem of reducing environmental risks in the process of functioning of the transport enterprise has been considered. The causes of risks due to wear and tear of vehicles have been analyzed. The directions of reducing environmental risks through the use of piggyback transportation of cargo have been considered. The economic and ecological advantages of using this method of transportation organization in order to reduce the volume of emissions of pollutants into the environment during the operation of vehicles have been analyzed. Based on the study of the functioning of a typical transport enterprise from the perspective of eco-oriented development, two potential strategies of the enterprise, based on the mechanisms of using secondary resources, have been presented.